2012
DOI: 10.1111/j.1365-2885.2012.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with the demonstration of bioequivalence of intramammary products in ruminants

Abstract: This article explores the numerous challenges encountered when the goal is to demonstrate bioequivalence (BE) between test and reference intramammary (IMM) products in ruminants. Numerous pathophysiological factors of mastitis and physicochemical properties of IMM formulations are implicated in the difficulties in confirming BE for this dosage form. Advantages and disadvantages of current BE study designs are discussed, and alternative perspectives are outlined. Ongoing and future research increasing our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…One study with 21 different commercially available intramammary products found that cows producing less than 9 kg of milk/d were more likely to have prolonged withholding times than higherproducing cows (Mercer et al, 1970). However, level of milk production may only partially explain variations in excretion rates as several high-producing cows were reported to have slow drug elimination (Mercer et al, 1970;Lainesse et al, 2012). Table 3 presents 5OH milk concentrations and the number of cows with milk concentrations greater than the tolerance limit of 2 μg/kg following intravenous, intramuscular, and subcutaneous administration at various sampling times.…”
Section: Milkmentioning
confidence: 99%
“…One study with 21 different commercially available intramammary products found that cows producing less than 9 kg of milk/d were more likely to have prolonged withholding times than higherproducing cows (Mercer et al, 1970). However, level of milk production may only partially explain variations in excretion rates as several high-producing cows were reported to have slow drug elimination (Mercer et al, 1970;Lainesse et al, 2012). Table 3 presents 5OH milk concentrations and the number of cows with milk concentrations greater than the tolerance limit of 2 μg/kg following intravenous, intramuscular, and subcutaneous administration at various sampling times.…”
Section: Milkmentioning
confidence: 99%
“…The AB guideline, does not contain much information about specific kinds of drugs for veterinary use. These include, for example, drugs administered intramammary or vaginally (Lainesse et al, 2012). The guideline does not at all bring up the subject of conducting AB drugs used with fish or bees.…”
Section: Discussionmentioning
confidence: 99%
“…However, extrapolation of data from bovine studies in regard to IMM administration of drugs in small ruminants may not be appropriate owing to interspecies differences and differences in the mastitis status of individual animals. 103,104 Although the gross composition of caprine milk is similar to that of bovine milk, there are some differences that may affect the absorption, distribution, and elimination of drugs following IMM infusion. The composition of the casein and whey protein fractions of caprine milk differs from that of bovine milk, and caprine milk has a higher proportion of free fatty acids and smaller fat globules than bovine milk.…”
Section: Combined Florfenicol-flunixin Meglumine Formulation-mentioning
confidence: 99%